Modification of Road Bitumen with Partial Desulfurized Crumb Rubber - Simona-Bianca Ghimiș; Gabriel Vasilievici; Andreea-Luiza Mîrț; Emilian Zaharia; Dorin Bomboș (Proceedings)
Incorporating crumb rubber into road bitumen represents a fundamental advancement in enhancing pavement performance and managing tire waste. While poly(styrene-butadiene-styrene) is a common choice for enhancing elasticity, its inherent limitations and environmental implications necessitate the exploration of alternatives. This study introduces the development of a novel crumb rubber derivative with superior elastic properties. The resulting modified bitumen exhibited a 58.3% reduction in crumb rubber sulfur content and a consistent asphaltene content of 18.7 ± 0.2%, ensuring its homogeneity. This research marks an advancement in producing elastic bitumen for specialized applications, contributing to sustainable road construction practices.